Enhancing Different Skill Sets of Engineering Students through Project based Interdisciplinary Approach - A Case Study of Azadi Ka Amrit Mahotsav Project - Parmar, Rahul; Patel, Vimalkumar N; Kapadiya, Jaykumar; Vekariya, Jaykumar; Zaveri, Priyank; Oza, Virang H; Gandhi, Vaibhav; Jadeja, Siddharthsinh (Journal of Engineering Education Transformations, 2025)
Technology and the availability of information have shifted the focus of researchers of engineering education towards experiential learning, a three-dimensional learning approach for students’ engagement and development. The MIT report on The Global State of the Art in engineering education also shows the importance of experiential learning as a pedagogical tool for engineering education. Many researchers have discussed how this pedagogical tool is used to develop various skills like leadership, decision-making, teamwork etc. However, how experiential learning is mapped with learning outcomes and strategy for their assessment is yet not developed and discussed in depth. This research paper discusses the learning of students while working on the project undertaken under Mission Amrit Sarovar- Jal Dharohar Sanrakshan-2022 as part of the Azadi Ka Amrit Mahotsav initiative by the Government of India to rejuvenate ponds, advocating sustainability, and enhancement of analytical skills. The paper also discusses how effectively various learning aspects and understanding of all participating students would be mapped with required skill sets. The survey instrument has captured the detailed response to do an analysis of learning and later on, that has been mapped with required skill sets. Moreover, activities were designed with a perspective to provide experiential learning for students to engage with relevant officials, enhancing their communication and presentation skills. This also facilitates interdisciplinary collaboration in addressing environmental challenges and conserving valuable natural resources. The findings provide a direction for field-academic scenarios with practical knowledge and foster students’ ability to contribute to real-world problems.